Correction to: Understanding the phenotypic spectrum and family experiences of XYY syndrome: Important considerations for genetic counseling - Colleen Jodarski; Rylee Duncan; Erin Torres; Rachel Gore; Armin Raznahan; Morgan Similuk (Journal of Community Genetics, 2023)

Understanding the phenotypic spectrum and family experiences of XYY syndrome: Important considerations for genetic counseling - Colleen Jodarski; Rylee Duncan; Erin Torres; Rachel Gore; Armin Raznahan; Morgan Similuk (Journal of Community Genetics, 2023)
XYY syndrome is characterized by a variable neurodevelopmental phenotype, with features including developmental delays, cognitive impairments, and an increased risk for mental health conditions. There are two recent developments that have primarily motivated this review. The first is the increased use of non-invasive prenatal screening (NIPS), which will likely result in more individuals being diagnosed with XYY prenatally. As such, health care providers (HCPs) both within genetics and outside of the specialty are more likely to encounter this diagnosis in the future. The second is advances in the understanding of the phenotypic variability of XYY through biobank and deep phenotyping efforts. As the phenotypic spectrum of XYY syndrome continues to expand, families will face greater uncertainty when receiving this diagnosis. Given both of these developments, HCPs will need to have up-to-date and accurate information about XYY to better counsel families. Furthermore, the ability to employ effective counseling techniques, such as anticipatory guidance, will aid in supporting and guiding families through the diagnostic journey. This review aims to provide insight on the neurodevelopmental and psychosocial aspects of XYY syndrome by discussing current research and borrowing from the relevant psychosocial literature of other genetic conditions. In this way, we hope to equip HCPs with the ultimate goal of improving the care and support provided to individuals with XYY and their families.